Rethinking love, independence, and speciesism in assistance dog discourse - Taş, Birkan (Frontiers in Sociology, 2025)
This paper challenges the prevailing belief that assistance dogs inherently love their roles, arguing that the notion of “unconditional love” in discourses on assistance dog perpetuates a human-centric perspective and reinforces speciesism. It emphasizes the importance of recognizing the affective experiences of these working animals and of acknowledging the interdependence between people with disabilities and assistance dogs. The paper has four main objectives: (1) critiquing the concept of unconditional love attributed to assistance dogs, (2) recognizing the physical and affective labor of assistance dogs, (3) highlighting the importance of interdependence over independence, and (4) exploring the intersections of ableism and speciesism in the context of assistance dogs. By examining the role of love as a narrative-framing device, the paper aims to reveal how anthropocentric viewpoints often obscure the exploitation of assistance dogs. Incorporating insights from human-animal studies and disability studies, the paper seeks to enrich sociological research on emotions and power structures, advocating for a shift toward valuing the labor and wellbeing of assistance dogs. This approach challenges the liberal ideology of independence and promotes a more inclusive understanding of interspecies relationships, ultimately enhancing the sociological study of emotions, and intersections between sociology, disability studies, and human-animal studies.